Multidimensional Assessment of Women’s Empowerment in India: A Socio-Spatial Perspective Using NFHS-5 Data - Pandey, Shrinkhla; Kumar, Shubham; Rai, Gayatri (Sociedade & Natureza, 2025)
Women’s empowerment plays a vital role in advancing socio-economic development and promoting gender equality. In the Indian context, empowerment is shaped by factors such as educational attainment, economic participation, access to healthcare, and decision-making capacity. However, these determinants are unevenly distributed across regions, resulting in notable socio-spatial disparities. This study draws on data from the National Family Health Survey (NFHS-5, 2019–2021) to assess regional variations in women’s empowerment across three core dimensions: freedom of mobility, autonomy in household decision-making, and attitudes toward domestic violence. To quantify these dimensions, three composite measures—the Mobility Index, Household Autonomy Index, and Domestic Violence Attitude Index—were developed and applied across states. The analysis reveals distinct regional patterns. Southern states and several northeastern states exhibit relatively high levels of household autonomy, reflecting stronger educational and socio-economic conditions. However, mobility patterns within these regions show variability: states such as Manipur and Meghalaya display high levels of women’s movement outside the home, whereas some tribal-dominated areas demonstrate restricted mobility due to traditional norms and geographical constraints. Conversely, several northern states show limited mobility despite moderate household decision-making autonomy, suggesting deeply rooted patriarchal structures that constrain women’s public presence. Attitudes toward domestic violence further highlight cultural differences, often diverging from patterns of autonomy or mobility. Acceptance of domestic violence remains comparatively higher in northern and central states, indicating persistent gender norms that hinder empowerment even when other indicators show improvement. Based on the composite indices, states were categorized into high, medium, and low empowerment levels. Kerala, Tamil Nadu, and Goa consistently ranked in the high category, reflecting comprehensive social development. Maharashtra and Gujarat demonstrated intermediate progress, while Uttar Pradesh, Bihar, and Rajasthan remained in the low category. These spatial disparities reinforce the long-standing divide between the southern/northeastern states and the EAG/northern states, underscoring the need for region-specific policies that address structural inequalities, cultural barriers, and institutional gaps.